The National Contact Points and its Role in Settling labor Disputes Related to Multinational Corporate Social Responsibility Issues - Bourezig, Kheira (Journal of Legal Studies and Researches, 2022)
The National Contact Points is a non-judicial grievance mechanism to be established by governments that adhere to the OECD Guidelines for Multinational Corporations, whose job it is receive complaints against any enterprise working in or from the territory of the Compliant State that didn't comply with the Guidelines. Thus, it is one of the modern amicable ways to settle labor disputes arising from the application of SR in specific instance.